Collaboration of Thai Alternative Education Network Partners: A Case Study of Indigenous Education Network Partners and Children and Juvenile Network Partners - Maneeshine, Kamonchanok; Thummachote, Ravipa (The Journal of Development Administration Research, 2023)
This academic article has the objective (1) To study the development of collaboration among alternative education network partners. (2)To study the factors leading to the collaboration of alternative education network partners. (3) To study the collaboration process among alternative education network partners. (4) To study the output, results, obstacles of the collaboration process of the alternative education network partners. In regard to the research methodology, the qualitative research was used with the method of case study. Two cases were selected for the study: the indigenous education network and the children and juvenile network. 30 people Data were collected using the technique of in-depth interview. 1.the development of the collaboration of Thai alternative education network partners commenced prior to the collaboration period.. Later, they grouped together as a network of those having the same ideology in the alternative education approach. 2.In regard to factors leading to the collaboration of Thai alternative education network partners, the following was found. The most important factors are the law and policy. Concerning the collaboration process of Thai alternative education network partners, the following was found. The most important essence in the collaboration process is the mutual ideology of network members as well as honesty in the operations to ensure the success of the goals mutually set. 4.The main outcome resulting from the collaboration of Thai alternative education network partners is the mutual exchange of knowledge. In the collaboration, obstacles are in the matter of the differences of members. That affects the understanding or operational guidelines which may be from misunderstanding. The networks regularly organized discussions to foster mutual understanding. Finally, the collaboration of Thai alternative education network partners is for the outcome of learners’ happiness as a result of receiving education of their own interests and appropriate with the learners’ potentialities. The public sector should provide opportunities for the participation from other sectors in the formulation of policy or in an issuance of the law concerning education, especially from stakeholders or those directly affected by such problems. Various sectors in the society consist of those who have knowledge and expertise in various issues occurring in their own areas. They therefore have the information for policy formulation and implementation to be in consonance with the problems and needs in a true manner.